معركة النهروان (38هـ/ 658م): دراسة تحليلية للمقدمات والمآلات والتداعيات في ضوء تعدُّدية الروايات التاريخية - الريامي, علي بن سعيد; اليعربي, يونس بن مطر (مجلة الدراسات الإنسانية والأدبية, 2025)
هدفت هذه الدراسة إلى تحليل المقدمات التاريخية لمعركة النهروان 38هـ/ 658م، وتداعياتها على البنية السياسية والفكرية للمجتمع الإسلامي المبكر؛ مع تقديم قراءة جديدة تعتمد إلى مصادر متنوعة، بما فيها المصادر الإباضية التي أُهمِلَت في دراسات سابقة. تكمُن أهمية هذه الدراسة في الكشف عن جذور النزاعات السياسية والفكرية التي شَهِدَها الإسلام المبكر، وانعكاساتها على تشكيل المفاهيم المتعلقة بالشرعية السياسية وطاعة الحاكم، فضلًا عن فهمِ تداعياتها على الواقع العربي والإسلامي المعاصر، كونِها تُسَلِّطُ الضوء على واحدة من أكثر المراحل تعقيدًا وحسَّاسيَّةً في التاريخ الإسلامي. فمن خلال دراسة معركة النَّهروان؛ يمكن فهمُ الجذور الأولى للنزاعات السياسية والفكرية التي ظهرت في الإسلام المبكر، ومدى تأثيرها في ظهور ما عُرِفَ "الفِرَق الإسلامية" اعتمدت هذه الدراسة المنهجَ التاريخي التحليلي، من خلال تتبُّع الروايات التاريخية ومقارنتها نقديًّا؛ مع التركيز على تجاوز التَّحيُّز الأيديولوجي ودمج وجهات نظر المصادر المختلفة. ومن أبرز ما توصلت إليه هذه الدراسة من نتائج أنَّ معركة النَّهروان مثَّلت تحوًّلًا جوهريًّا في علاقة السُّلطة بالمعارضة، وأسهمت في ترسيخ الانقسامات الفكرية والسياسية، وأكدت ضرورة الاعتماد إلى مصادر متعددة لتقديم رُؤية شاملة للأحداث.الكلمات المفتاحية: النَّهروان؛ صِفِّين؛ السُّنَّة؛ الشِّيعة؛ الإباضية.
Keywords: Fitnah

الفتنة من منظور قرآني؛ دلالاتها ومعانيها - ناصر, حمد صالح (الحياة, 2017)
Keywords: Fitnah

Ali-Muâviye Mücâdelesi ve Harici Ayrilmasinin îbâdî kaynaklarin isiğinda incelenmesi - Veccia Vaglieri, Laura (Ankara Üniversitesi Ilâhiyat Fakültesi Dergisi, 1973)
Keywords: Fitnah

Khilāfat ʿUthmān wa-ʿAlī min Kitāb Kashf al-Bayān, Ta’līf Abī Saʿīd Muḥ. b. Saʿīd al-Azdī al-Qalhātī - Ibn ʿAbd al-Jalīl, Muḥammad (Ḥawliyyāt al-Jāmiʿa al-Tūnisiyya, 1974)
Chapters 17-22 from K. al-Kashf wa’l-Bayān. based on MS Or. 2606 in the British Museum.
Keywords: Fitnah

The significance of the slogan Lā Ḥukma illā li’llāh and the references to the Ḥudūd in the Traditions about the Fitna and the murder of ʿUthmān - Hawting, Gerald R. (Bulletin of the School of Oriental and African Studies, 1978)
Keywords: Fitnah

Traduzione di passi riguardanti il conflitto ʿAlī-Muʿāwiya e la secessione khārigita dal Kitāb al-Jawāhir di al-Barrādī - Veccia Vaglieri, Laura (Annali dell'Istituto Universitario Orientale di Napoli, 1953)
Translations with comments and annotations from: Barrādī: K. al-Jawāhir (lith., Cairo 1302/1884-5, 111-147) (1-73); Shammākhī: K. al-Siyar (Cairo 1301, 45-56) (74-87); Naṣr b. Muzāḥim al-Minqarī: Waqʿat Ṣiffīn (88-92); index of names and Arabic terms in Veccia Vaglieri 1952 and in this article (92-98).
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Fitnah

Il conflitto ʿAlī-Muʿāwiya e la secessione khārigita riesaminati alla luce di fonte ibāḍite - Veccia Vaglieri, Laura (Annali dell'Istituto Universitario Orientale di Napoli, 1952)
the ʿAlī - Muʿāwiya conflict is a historical moment which is interesting not only owing to the very serious consequences it brought in the Islamic world, but because it gives rise to a lot of problems still unsolved or whose solution is not satisfactory. The islamists had till now for the study of the Caliphate of ʿAlī availed themselves only of philo-alid or philo-umayyad sources. The author has observed, in the course of her reading Ibāḍī texts, that two of them, the Jawāhir of al-Barrādī and the Siyar of al-Shammākhī, have handed down to us on this period of history very ancient Khārijite or philo-khārijite traditions taken from K. al-Nahrawān which was probably composed during the first half of the 2nd century A.H. The above said traditions have been of great importance to the author for two reasons, i.e.: they allowed her to fix the point of view of the Khārijites, a vague point till now; and have supplied her with the key to enable her to understand many passages of other sources (Ṭabarī, Balādhurī, Dīnawarī, Yaʿqūbī, Masʿūdī, etc. already studied by the islamists, and the Waqʿat Ṣiffīn of Naṣr b. Muzāḥim almost not utilized till now, while it supplies with information of the greatest importance).
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Fitnah

The Siffin Arbitration Agreement - Hinds, Martin (Journal of Semitic Studies, 1972)
Keywords: Fitnah

معركة النهروان 38 هـ - سليمان, أسامة بن علي (التوحيد, 2012)
Keywords: Fitnah

التحكيم في معركة صفين : أسبابه ونتائجه - البشير, عبدالفتاح محمد الكباشي (مجلة جامعة أم درمان الإسلامية, 2005)
Keywords: Fitnah

الفتنة الكبرى - الجورشي, صلاح الدين (الإجتهاد, 1991)
Keywords: Fitnah

خلافة عثمان وعلي من كتاب "الكشف والبيان" - ابن عبد الجليل, محمد (حوليات الجامعة التونسية, 1974)
Keywords: Fitnah

The Murder of the Caliph 'Uthmân - Hinds, Martin (International Journal of Middle East Studies, 1972)
The murder of ‘Uthmân was an important turning-point in Islamic history, and the story of how opposition in the provinces, particularly Egypt, combined with opposition at Medina itself and brought about the Caliph's death has been repeated many times. Accounts in sources such as al-Tabarî's History and al-Balâdhurîs Ansâb al-ashrâf bring together much transmitted detail concerning this dénouement. Caetani's monumental Annali dell'Islam serves as an extensive compilation of such detail, and Wellhausen, Levi Delia Vida, Gibb, Veccia Vaglieri and Petersen are only some of the other modern scholars who have commented on the event. Perhaps Professor Gibb best expresses the current view of the background to it in his thought-provoking article entitled ‘An interpretation of Islamic history’, where he sees in the caliphate of 'Uthmân a conflict between two main parties, the Meccans and the ‘tribesmen’. He points out that the Meccan merchants had been swift to seize the opportunities of wealth which arose in the immediate post-conquest phase, and goes on to say that in the course of 'Uthman's caliphate there arose at Medina ‘growing resentment at the rapid affirmation of Meccan political control… and the economic exploitation of the empire. Open discontent was first expressed by several religious personalities, whose conscience was shocked by the worldliness and grasping materialism displayed in the name of Islam. But these only provided a rallying-cry and a cloak for the material grievances of the tribesmen and Medinians, who swung into line behind them.’ Gibb therefore sees a total of four alignments, of which the Meccans and the tribesmen were the main parties, while the Medinans and the so-called religious party were secondary in importance.
Keywords: Fitnah

The Banners and Battle Cries of the Arabs at Ṣiffīn - Hinds, Martin (al-Abhath, 1971)
Keywords: Fitnah

ʿAlī and Muʿāwiah: The rise of the Umayyad caliphate 656-661 - Petersen, Erling Ladewig (Acta Orientalia, 1958)
Keywords: Fitnah